(untitled) (Journal of the Digital Humanities Association of Southern Africa, 2024)
Urbanisation in South Africa is expanding at an alarming rate. With the ever-expanding growth of urban areas, it is essential to understand how urban sites can function as greenspaces that provide wildlife habitats, biodiversity hotspots, as well as act as movement corridors for birds and mammals. In this study, I investigate the grounds of the Fort England Psychiatric Hospital as a small-scale greenspace. The hospital is located in Makhanda (formerly Grahamstown), in the Eastern Cape Province of South Africa. I propose an investigation of the site that is informed by a branch of digital environmental humanities that uses digital technologies to mobilise collective action in the conservation and stewardship of a greenspace. To this end, the article calls for a deep mapping of the site to achieve a twofold research objective. First, to study the biodiversity of the site and explore the possibility that it could offer a refuge for threatened species. Second, to call for an inclusive management plan for the greening and conservation of the site. To substantiate, the site is of importance for human use, environmental history, as well as for fauna and flora species. Accordingly, the site’s management plan must engage, accommodate and negotiate a diverse set of interests, as well as mobilise action from various members of the community.